Pengaruh Efikasi Diri terhadap Kreativitas Guru - Jauhari Hamid Ripki, Ahmad; Nurlaelah, Nurlaelah; Triyono, Ageng (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this research is to determine the influence of self-efficacy on teacher creativity in the learning process. The research used is a type of quantitative research using a causality approach. The instrument used to collect data was a questionnaire. Questionnaires were given to 210 teachers who were the research sample using a survey method with one-way analysis. The collected data was analyzed using the Pearson Product Moment (PPM) statistical test which was then used as a basis for drawing conclusions regarding the hypothesis used. The results of hypothesis testing show that self-efficacy has a direct and significant effect on teacher creativity. The self-efficacy indicator that has the most influence on teacher creativity is the Personal Skills indicator.